The attitudes of elementary school students towards physical education teachers - Miličković Velimir; Vukićević Veljko; Zečević Stanko; Vignjević Slobodan (College of Sports and Health, Belgrade, 2019)
The aim of the study was to determine the factor structure of the assessment scale of the Physical Education Teacher Attitude Questionnaire, as well as to ascertain the existence of gender, age, and differences in whether students practice some sport outside of school or not, in terms of attitudes toward different physical education teacher competences. A sample of 119 students of both genders, grades 5 through 8, was assigned a USF assessment scale, modeled on existing instruments for assessing student attitudes toward physical education and physical education teachers. The factor structure was determined by using factor analysis. The ANOVA results for gender differences indicate that there are no statistically significant differences in the attitudes of students towards the competences of physical education teachers. ANOVA results for differences between coaching students and non-coaches suggest that there are statistically significant differences between these groups of respondents regarding the factor of socio-emotional competence of teachers, in the sense that students who train a sport are more inclined towards the socio-emotional competences of teachers. The ANOVA results for age differences indicate that there are statistically significant differences between younger and older students, regarding both factors, in the sense that younger students are more inclined towards both the socio-emotional and professional competences of physical education teachers. Attitudes towards the teacher provide valuable information about what students think and feel about them, thus creating adequate conditions for effecting change and improving both teaching and relationships with students.